Stabilisasi Tanah Ekspansif Menggunakan Limestones Sebagai Subgrade Perkerasan Jalan Pada Proyek Jalan Tol Seksi 6a Paket Sumedang – Dawuan - saepudin, uu; sutrisna, dedi; binter, aan (Jurnal Ilmiah Teknik Sipil, 2023)
The problems that occur in the Toll Road Project Section 6a of the Sumedang – Dawuan package are subgrade soils including expansive soil types. Where the type of expansive soil is a soil type that is not good with very high clay content, expansion and shrinkage. This potential for shrinkage causes less stability in the road construction so that it affects the safety and comfort of traffic. The general technical properties of expansive soils are that they have a fairly high moisture content and low bearing capacity. Because of these properties, expansive soils are classified as poor soils to be used as subgrades. One way to overcome this is by improving the soil or so-called soil stabilization. In this study, the material used for stabilizing the expansive soil is limestone. Limestone or limestone is a carbonate rock that is formed biologically and biochemically.This research was conducted with the aim of knowing the effect of adding limestone to the physical properties of expansive clay and knowing the optimum level of addition of limestone so as to produce a maximum increase in the stability of the road construction subgrade. The research method used is the experimental method. The study was designed with 5 treatments, namely 0%, 25%, 50%, 75% and 100% of the use of limestone on expansive clay soil.The results showed that the use of limestone as a stabilizing agent for clay in the Section 6a of the Sumedang – Dawuan Toll Road Project affects the physical and mechanical properties of the expansive clay. Where the higher the addition of limestone, the smaller the liquid limit (LL), plasticity limit (PL), moisture content and swelling, while for specific gravity, compaction and CBR the higher. The use of limestone in the Toll Road Project Section 6a Sumedang – Dawuan Package optimum 75% with a ratio of 25% expansive clay with a CBR value of 3.75% < 6% (Minimum requirement of CBR value for road pavement subgrade) and produces a development value ( swelling) 3.85% > 1.25% (maximum limit conditions for pavement subgrade swelling). The CBR value and swelling (swelling) do not meet the requirements as a subgrade for road pavement, in accordance with the expressway technical specifications for a minimum subgrade density of 100℅, a minimum CBR of 6℅ and a maximum swelling of 1.25℅.